2018
DOI: 10.1007/s13197-018-3188-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activity of bioactive prodigiosin produces from Serratia marcescens using agricultural waste as a substrate

Abstract: The objective of this investigation was to explore the antioxidant and antimicrobial property of bioactive prodigiosin produced from using rice bran. The antioxidant potential of prodigiosin was examined by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2'-azino-bis 3-ethylbenzthiazoline-6-sulfonic acid (ABTS) radical scavenging method via UV-visible, electron spin resonance spectrum (ESR), cyclic voltammetry and excitation emission spectrum. The antimicrobial activity of prodigiosin was examined against foodbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…activity of the DPPH radical scavenging capacity of PG to be 86%, 99%, and 98%, respectively. However, few data on the ABTS radical scavenging of PG have been reported so far [35]. Notably, almost all of the studies did not report the IC50 values on antioxidant activity of PG [11].…”
Section: Antioxidant and Anticancers Activities Of Purified Pgmentioning
confidence: 99%
“…activity of the DPPH radical scavenging capacity of PG to be 86%, 99%, and 98%, respectively. However, few data on the ABTS radical scavenging of PG have been reported so far [35]. Notably, almost all of the studies did not report the IC50 values on antioxidant activity of PG [11].…”
Section: Antioxidant and Anticancers Activities Of Purified Pgmentioning
confidence: 99%
“…Prodigiosin has been investigated for its vast biological activities, including insecticidal, antioxidant, algicidal, antimicrobial, anti-inflammatory, antimalarial, anticancer, immunomodulatory, and anti-diabetic activities [19,37]. With the aim of evaluating the prodigiosin newly synthesized in this study for potential use in anticancer drugs, prodigiosin was tested for its inhibition against some cancerous cell lines, including A549, Hep G2, MCF-7, and WiDr.…”
Section: Evaluation Of Inhibitory Effect Of Prodigiosin Against Cancementioning
confidence: 99%
“…PSN0.75 had the highest DPPH value comparing with other nectar samples recording 88.17% at 120 min of incubation time, while, prodigiosin recorded 66.87 % and ascorbic acid 93.27%. Arivizhivendhan et al, (2018) reported that the bioactive prodigiosin extracted from Serratia effectively scavenged the free radical and inhibited the bacterial growth in food products. Some amino acids, such as histidine, tyrosine, methionine, and cysteine, have been reported to show antioxidant activity (Abdel-Hamid et al, 2017;Osman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The prodigiosin having pyrrolyl pyrromethane skeleton was first charactarized from S. marcescens and reported to be antimicrobial including antibacterial activity (Gulani et al, 2012), antifungal, antiproliferative agent and immunosuppressive (Khanafari et al, 2006). Prodigiosin has prohibited the growth of food borne pathogens effectively and the shelf life of the food was also extended significantly (Arivizhivendhan et al, 2018). The prodigiosin of Serratia marcescens IBRL USM 84 exhibited a broad inhibitory spectrum activity against more bacteria (Nwankwo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%